Quantification of the Nucleophilic Reactivities of Ethyl Arylacetate Anions1. Issue 20 (24th May 2013) - Corral‐Bautista, Francisco; Mayr, Herbert
Abstract: The kinetics of the reactions of substituted ethyl arylacetates with quinone methides and structurally related diethyl benzylidenemalonates have been studied in DMSO. The second‐order rate constants (lg k 2 ) correlated linearly with the electrophilicities E according to the linear free‐energy relationship lg k 2 = s N ( N + E ), allowing us to determine the nucleophilicity parameters N and s N for these anions. The nucleophilic reactivities of the carbanions vary from N = 27.5 for the parent compound to N = 20.0 for the 4‐nitro‐substituted derivative. Abstract : The kinetics of the reactions of the anions of ethyl arylacetates with quinone methides and diethyl benzylidenemalonates were investigated in DMSO solution. The resulting rate constants follow the linear free‐energy relationship lg k 2 = s N ( N + E ), which allowed us to derive their reactivity parameters N and s N .